Sistem Business Intelligence untuk Evaluasi Kinerja Widyaiswara Kementerian Agama - Muhamad Noval (Ikatan Ahli Informatika Indonesia (IAII), 2020)
The Religious Research, Development and Training Agency of the Ministry of Religious Affairs as a supervisory unit for Widyaiswara functional positions, has the task of evaluating the performance of Widyaiswara of the Ministry of Religious Affairs. That demands the availability of a need for reports or data that presented quickly and accurately when the Widyaiswara performance evaluation process is conducted every year. The problem that occurs these days is that the data on the result of credit score of Widyaiswara assessment are stored in an unstructured excel file. This study utilizes the data warehouse and business intelligence in the process of Widyaiswara performance evaluation. The OLTP (Online Transaction Process) Data that presented for data warehouse is the result of credit score of Widyaiswara assessment. The planning of data warehouse conducted through nine-steps methodology that created by Kimball and Ross, then those data were analyzed using OLAP (Online Analytical Processing) in the application of qliksense in the form of dashboard business intelligence to present the data in a faster visual form. The result, giving the information to the leader to evaluate the performance of Widyaiswara, especially in making decision such as circular letter to improve the quality of Widyaiswara performance, the minimum score limit in the performance agreement, reward in the form of certificate of appreciation for the highest score and punishment in the form of warning letter for the low total score.